Intervenciones de enfermería en el adulto mayor con cáncer de próstata - Bonifaz Pañora, Lucero Aracely (2020)
This bibliographical entitled "Nursing interventions in the elderly with prostate cancer" is carried out, a pathology that defined as a single histological disease, with marked clinical heterogeneity, ranging from a disease without clinical repercussion to a disease that causes death rapidly, it had a high incidence, considering that the malignant tumor in this type of cancer took approximately five years to metastasize, worldwide it is in second place with approximately 7.7 million deaths and, according to calculations for the year 2030 it will exceed 13.1 million, in Ecuador, in 2018 3322 cases reported. For this reason, the importance of having a standardized care plan in order to achieve the correct quality of care. The main objective of this work was to identify, through the bibliographic review, nursing interventions in the elderly with prostate cancer. Several documents selected, from which 105 articles took for the bibliographic review of the scientific bases: Scielo, Scopus, Pubmed, Elserver, Ebsco, Google academic and Latindex; which allowed the triangulation and analysis of the same to obtain the pertinent information. The main nursing actions analyzed, according to the authors' coincidence, related to personalized interview, patient and family counseling, general physical examination, pain assessment, medication administration, palliative care, emotional support, interpretation of laboratory data and records of nursing.